METHODS OF EXTRACTION OF ETHYL MERCAPTAN FROM ORGANOSULFUR COMPOUNDS IN GAS CONDENSATE - Tilloyeva, Shaxnoza Fakhritdinovna; Sharipov, Kahramon Kandiyorovich (INTERNATIONAL CONFERENCES, 2023)
The article is based on the use of extractors that select sulfur compounds from gas condensates. Aqueous solutions of sodium hydroxide, ethanolamines, dimethylformamide, diethylene glycol, dimethyl sulfoxide, etc. are offered as extractors. However, none of the extractors currently used meets all the necessary requirements - high solubility compared to sulfur compounds, high density, low viscosity, availability and low cost, lack of toxicity and corrosion properties.